Factors that Influence Purchasing Decisions at Shopee Marketplace during the Covid-19 Pandemic - Indrianto, Anggraeni Pratama; Yuwono, Efendi Sutopo (Jurnal Samudra Ekonomi dan Bisnis, 2022)
The Covid-19 pandemic has slowly changed people's behavior, one of which is making purchases. Many factors influenced a person to make purchases during the pandemic which the Shopee marketplace has responded well by providing various additional features to make it easier for consumers to shop from home. This study aimed to examine whether purchase intention is able to mediate the effect of perceived trust and perceived risk on purchasing decisions at the Shopee marketplace during the current pandemic. Purposive sampling technique was used to determining the sample. The results obtained were that perceived trust and the perceived risk had a significant positive effect on purchasing decisions either directly or through purchase intention as an intervening variable. The recommendation for Shopee is to focus more on minimizing the risk of its consumers, including the risk of being infected with Covid-19.